2019
DOI: 10.2147/phmt.s182296
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characteristics and health care utilization of otherwise healthy commercially and Medicaid-insured preterm and full-term infants in the US</p>

Abstract: Purpose This study examined health care utilization and costs during the first year of life for preterm and full-term infants in the US. Subjects and methods Preterm (<37 weeks gestational age [GA]) and full-term infants born 2003 to 2012 without complex medical conditions were identified in the MarketScan ® Commercial and Multi-State Medicaid claims databases using ICD-9-CM diagnosis and diagnosis-related grouping codes. Inpatient and outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, preterm infants require increased hospitalization length of stay, number of outpatient visits, pharmacy claims, and mean monthly health care costs (Fig. 2 ) compared to term infants [ 34 ].
Fig.
…”
Section: Impact Of Rsv Disease On Health Care Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, preterm infants require increased hospitalization length of stay, number of outpatient visits, pharmacy claims, and mean monthly health care costs (Fig. 2 ) compared to term infants [ 34 ].
Fig.
…”
Section: Impact Of Rsv Disease On Health Care Utilizationmentioning
confidence: 99%
“…
Fig. 2 Mean monthly health care cost per infant increases as the gestational age decreases [ 34 ]. FT full-term, US$ United States dollars, wGA weeks’ gestational age.
…”
Section: Impact Of Rsv Disease On Health Care Utilizationmentioning
confidence: 99%
“…These results are consistent with prior studies that have shown higher levels of all-cause resource use in the first year of life when comparing Medicaid-insured and commercially insured infants. 25 Additional research is necessary to determine whether differences in RSV-related healthcare resource use and RSVH severity in Medicaid-insured and commercially insured infants can be explained by baseline differences in the two populations or if additional factors contribute to disparities in RSV outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were conducted separately in Medicaid-insured and commercially insured infants due to underlying differences in the rate of hospitalization and healthcare resource use in the first year of life that have been previously described. 25 Descriptive analyses of baseline characteristics, including infant demographic, clinical, and birth hospitalization characteristics were conducted in term infants as well as in each subgroup of preterm infants. Chi-square or Fisher’s exact tests for nominal/categorical variables and t-tests for interval/continuous variables were used to compare patient characteristics in each subgroup of preterm infants to term infants.…”
Section: Methodsmentioning
confidence: 99%
“…The evidence that exists on outpatient services and prescription drug use shows that preterm neonates are high utilizers of these services [9][10][11][12][13][14]. Previous work, however, lacks important descriptors of outpatient followup immediately following NICU discharge, instead exploring service use months to years later [15]. This work also focuses on the smallest, most premature babies, who represent a high-risk, albeit small, proportion of infants in most NICUs.…”
Section: Introductionmentioning
confidence: 99%